2010
DOI: 10.21608/ejabf.2010.2058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fresh or dried garlic as a natural feed supplement on growth performance and nutrients utilization of the Nile Tilapia (Oreochromis niloticas)

Abstract: Effect of fresh or dried garlic as a natural feed supplement on growth performance and nutrients utilization of the Nile Tilapia (Oreochromis niloticas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
(26 reference statements)
1
3
0
Order By: Relevance
“…The highest SGR was recored in the GM4 group with 4% garlic meal inclusion (1.43 ± 0.03, %/day), followed by the control group (1.38 ± 0.07, %/day), GM2 (1.27 ± 0.08, %/day) and the GM6 (1.19 ± 0.03, %/day) groups, respectively (Table 3). This growth promotion effect of diets supplemented with garlic meal can be attributed to the improved feed efficiency, which is in agreement with the results in Nile tilapia (Diab et al, 2002;Shalaby et al, 2006;Mesalhy et al, 2008;Soltan and El-Laithy, 2008;Metwally, 2009;Abdel-Hakim et al, 2010), in Asian seabass (Talpur and Ikhwanuddin, 2012), in sterlet sturgeon (Lee et al, 2014), and in Seabass fry (Saleh et al, 2015), where the incorporation of different levels of garlic increased final weights and specific growth rates of fish. Soltan and El-Laithy (2008) reported that the incorporation of 1% garlic into diets improved survival rate of Nile tilapia.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The highest SGR was recored in the GM4 group with 4% garlic meal inclusion (1.43 ± 0.03, %/day), followed by the control group (1.38 ± 0.07, %/day), GM2 (1.27 ± 0.08, %/day) and the GM6 (1.19 ± 0.03, %/day) groups, respectively (Table 3). This growth promotion effect of diets supplemented with garlic meal can be attributed to the improved feed efficiency, which is in agreement with the results in Nile tilapia (Diab et al, 2002;Shalaby et al, 2006;Mesalhy et al, 2008;Soltan and El-Laithy, 2008;Metwally, 2009;Abdel-Hakim et al, 2010), in Asian seabass (Talpur and Ikhwanuddin, 2012), in sterlet sturgeon (Lee et al, 2014), and in Seabass fry (Saleh et al, 2015), where the incorporation of different levels of garlic increased final weights and specific growth rates of fish. Soltan and El-Laithy (2008) reported that the incorporation of 1% garlic into diets improved survival rate of Nile tilapia.…”
Section: Resultssupporting
confidence: 87%
“…Soltan and El-Laithy (2008) reported that the incorporation of 1% garlic into diets improved survival rate of Nile tilapia. Similarly, Abdel-Hakim et al (2010) found better achievements of dietary garlic on growth performance and feed utilization with low levels of garlic inclusion at 0.5 % level in tilapia. Better growth effects were found with higher incorporation levels of garlic meal in diets for Nile tilapia by Shalaby et al (2006), who tested garlic incorporation levels from 10 g/kg to 40 g/kg diet, and recommended the incorporation of 3% dietary garlic for an increased growth, reduction of total bacteria, and improvement of fish health and welfare.…”
Section: Resultsmentioning
confidence: 74%
“…A significant increase in growth, feed conversion and protein efficiency was shown in rainbow trout when fed diet with 1.0% garlic ( Nya and Austin, 2009 ). Abdel-Hakim et al (2010) reported that incorporation of garlic into Nile tilapia diets (diet with fresh garlic 3 g per kg) resulted in significant improvement in WG, feed conversion, protein efficiency and CF. Protein efficiency ratio and FE are utilized as quality indicators for fish diets and amino acid balance.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction procedures referred that, the higher body composition CP with moderate EE of tested fish were detected by low density rate of rearing fish fed diets supplemented with 10 g garlic/kg diet (122.88 and 3.92%). Abdel-Hakim et al, (2010) referred that addition of fresh or dried garlic (Allium sativum) in O. niloticus diets had no significant effects on fish whole bodies moisture; DM and ash contents, while it released significant effects on the whole body protein and lipid compared to control group. In addition, Xiang and Liu (2002) observed that, the supplementation of 25-100 mg garlic /kg in C. barchypomum diets improve the body protein and decrease the crude lipid content of experimental fish.…”
Section: Body Compositionmentioning
confidence: 99%